Carbon-coated nickel catalyst, preparation thereof and application of carbon-coated nickel catalyst in preparation of sorbitol through glucose hydrogenation

By adopting the preparation method of carbon-coated nickel catalyst, the stability and activity problems of Ni-based catalysts in glucose hydrogenation reaction are solved, and efficient catalytic performance and long-term stability of the Ni-based catalyst are achieved under harsh conditions.

CN119793464AActive Publication Date: 2025-04-11ZHEJIANG UNIV OF TECH
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411996311.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-11
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

The existing Ni-based catalysts have problems such as poor stability, easy loss of active components and oxidation in glucose hydrogenation reaction, resulting in a decrease in conversion rate.

Method used

By using the preparation method of a carbon-coated nickel catalyst, a nickel catalyst with an external carbon layer is formed by impregnation and high-temperature calcination of a supported nickel catalyst and soluble carbohydrate carbon source compound, thereby improving the stability and activity of the catalyst.

Benefits of technology

Under high temperature and high pressure and weak acid conditions, the carbon-coated nickel catalyst exhibits good catalytic hydrogenation performance, maintains long-term cycle stability and regeneration performance, and significantly improves the conversion of glucose and the selectivity of sorbitol.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005224581990000101
    Figure BDA0005224581990000101
  • Figure BDA0005224581990000111
    Figure BDA0005224581990000111
  • Figure BDA0005224581990000161
    Figure BDA0005224581990000161
Patent Text Reader

Abstract

The invention discloses a carbon-coated nickel catalyst, preparation thereof and application of the carbon-coated nickel catalyst in preparation of sorbitol through glucose hydrogenation. The preparation method comprises the following steps: 1, preparing a supported nickel catalyst; 2, uniformly mixing the supported nickel catalyst with water, adding a soluble saccharide carbon source compound, dipping at room temperature for 4-10 hours, and performing vacuum drying until moisture is dried to obtain a dried product; and roasting the obtained dried product for 4-10 hours at a high temperature of 400-900 DEG C in an N2 atmosphere to finally obtain the carbon-coated nickel catalyst. The invention provides the application of the carbon-coated nickel catalyst in preparation of sorbitol through glucose hydrogenation, and the carbon-coated nickel catalyst has good stability and target product selectivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of chemical industry and relates to a carbon-coated nickel catalyst and a preparation method thereof and application thereof in the reaction of preparing sorbitol by hydrogenating glucose. Background Art

[0002] Catalytic hydrogenation is a key step in the production of many bulk and fine chemicals. When there are multiple reducible functional groups in the reactants, specific groups need to be selectively hydrogenated to produce high-value chemicals. Supported nanometal catalysts are one of the most important hydrogenation catalysts and are widely used in industrial production. However, under some harsh reaction conditions, catalysts are prone to deactivation due to carbon deposition, sintering, poisoning, and leaching of active components. These phenomena not only increase the cost of industrial production, but also seriously affect the quality of high-end fine chemicals such as pharmaceuticals and electronic chemicals.

[0003] Inventing a supported noble metal catalyst with good catalytic hydrogenation activity and stability in harsh environments has far-reaching significance. People have proposed that graphene shells completely encapsulate transition metals (TMs) to prevent direct contact between metals and the external environment. This encapsulated catalyst encapsulates nanomaterials in a graphene shell, and the internal nanoparticles and the outer graphene shell layer interact strongly through chemical bonds or other forces. The graphene shell acts as a barrier in the catalytic reaction to prevent the encapsulated nanoparticles from oxidation, loss, agglomeration, etc.

[0004] Sorbitol is the most widely used polyol in industries such as food, medicine, cosmetics and chemicals. It can be used as a humectant, sweetener, texture agent, softener and the production of vitamin C, etc., and has broad development prospects. In the preparation of sorbitol from glucose as raw material, the industry is currently mainly in the form of catalytic hydrogenation, and the catalyst used is a noble metal Ru-based catalyst and a Ni-based catalysis. Although Ru-based catalysts show excellent activity and stability in hydrogenation reactions, they are not suitable for large-scale industrial applications because of their high price and low resource reserves. Ni-based catalysts have always been a hot topic of research due to their low price, abundant resources and good hydrogenation activity, but in glucose hydrogenation reactions, Ni-based catalysts still have problems such as poor stability, easy loss and oxidation of active components.

[0005] The Chinese patent with patent number CN 104107691A discloses a new Ru / CNTs catalyst and its preparation and use methods, that is, ruthenium trichloride is used as a metal precursor, dispersed on a modified carbon nanotube carrier treated with concentrated nitric acid, and a reducing agent is added under strong mixed alkaline conditions to obtain a Ru / CNTs catalyst with ruthenium as an active component. By regulating the catalyst preparation conditions and reaction conditions, compared with other Ru-based catalysts, it has higher catalytic activity and selectivity, and the reaction conditions are milder, but the production cost of the Ru-based catalyst is high, and its stability has not been evaluated.

[0006] A Chinese patent with patent number CN110465296A discloses a nickel-based glucose catalyst, which is mainly composed of main active components of nickel and nickel oxide, additives, silicon oxide and zirconium oxide. First, a catalyst precursor is obtained by microwave-assisted co-precipitation, and then the catalyst precursor is passivated and reduced to obtain a glucose hydrogenation catalyst. This catalyst overcomes the problem that skeleton nickel catalysts need to adjust the reaction stock solution to alkalinity before use, and also extends the service life of the catalyst to a certain extent. However, after 8 application experiments, the conversion rate of glucose decreased significantly.

[0007] Therefore, based on the above background, it is of great significance to design a low-cost, high-performance Ni-based catalyst for catalytic hydrogenation of glucose. Summary of the invention

[0008] The purpose of the present invention is to provide a carbon-coated nickel catalyst and a preparation method thereof and application thereof in preparing sorbitol by hydrogenation of glucose.

[0009] To solve the above-mentioned invention object, the present invention adopts the following technical solution:

[0010] In a first aspect, the present invention provides a method for preparing a carbon-coated nickel catalyst for preparing sorbitol by hydrogenation of glucose, comprising the following steps:

[0011] Step 1: Preparation of supported nickel catalyst: disperse the carrier in water, add nickel precursor solution, stir in a water bath at 70-90°C for 3-6h, then add ammonia water dropwise to adjust the pH to 12 to allow nickel ions to fully precipitate, continue stirring for 0.5-5h, cool to room temperature, filter, wash with water until neutral, and vacuum dry until the water is dried to obtain a dry product; calcine the obtained dry product at 500-800°C in an inert atmosphere or air atmosphere for 4-8h to obtain a calcined product, and finally transfer to a tubular furnace, introduce a constant H2 gas flow, program the temperature to 300-500°C for reduction for 3-9h to obtain a supported nickel catalyst, and the obtained catalyst is sealed with ethanol for preservation;

[0012] Step 2: Mix the supported nickel catalyst and water evenly, add a soluble sugar carbon source compound, soak at room temperature for 4 to 10 hours, and then vacuum dry until the water is dried to obtain a dry product; the obtained dry product is calcined at 400-900°C for 4-10 hours under a N2 atmosphere to finally obtain the desired carbon-coated nickel catalyst; the soluble sugar carbon source compound is selected from one of monohydrated glucose, soluble starch, monohydrated citric acid, PVP or sucrose; the mass of carbon element in the soluble sugar carbon source compound accounts for 10-50% of the mass of the supported nickel catalyst, preferably 20-50%, more preferably 35-50%, and further preferably 40-45%.

[0013] In the preparation method of the catalyst described in the present invention, the nickel precursor solution described in the present invention is prepared by dissolving a nickel precursor in a solvent; the present invention has no special requirements on the solvent and concentration of the nickel precursor solution, and those skilled in the art can prepare it conventionally according to actual needs. For example, the concentration of the nickel precursor solution in terms of nickel can be 0.1-0.5 g / mL; the nickel precursor is selected from Ni(NO3)2·6H2O, NiCl2·6H2O, Ni(CH3COO)2·6H2O or NiSO4·6H2O, etc., preferably Ni(NO3)2·6H2O or NiCl2·6H2O; the solvent depends on the type of nickel compound, and can be deionized water, ethanol, etc., and the present invention has no special requirements for this.

[0014] In the supported nickel catalyst prepared by the present invention, the carrier of the supported nickel catalyst is activated carbon, SiO2, TiO2 or diatomaceous earth.

[0015] In step 1 of the present invention, the carrier and the nickel precursor solution are fed according to the required theoretical loading amount of nickel, specifically, the theoretical loading amount of nickel = m Ni / m 载体 ×100%=20-45%, preferably 25-45%, more preferably 30-35%; wherein m Ni It refers to the mass of Ni element contained in the nickel precursor solution.

[0016] In the carbon-coated nickel catalyst prepared by the present invention, the surface carbon layer is obtained from different carbon precursors, and the carbon precursor is preferably glucose monohydrate or soluble starch, and glucose monohydrate is most preferred.

[0017] In step 1 of the present invention, the vacuum drying temperature is 60-100° C., and the drying time is 10-15 hours.

[0018] In step 1 of the present invention, the obtained dried product is calcined at 500° C. for 5 h in an inert atmosphere or an air atmosphere to obtain a calcined product, and finally transferred to a tubular furnace, a constant flow of H2 is introduced, and the temperature is programmed to 400° C. for reduction for 5 h.

[0019] In step 2 of the present invention, the mass ratio of the supported nickel catalyst to water is 1:50-300.

[0020] In step 2 of the present invention, the vacuum drying temperature is 60-100° C., and the drying time is 4-15 hours.

[0021] In step 2 of the present invention, during the high temperature calcination to form the carbon layer, the calcination temperature is 400-900°C, preferably 500-800°C, more preferably 550-650°C, and most preferably 600°C for 6h.

[0022] In the present invention, the inert atmosphere is one or more of nitrogen, argon and helium.

[0023] In a second aspect, the present invention provides a carbon-coated nickel catalyst prepared according to the preparation method described in the first aspect. The carbon-coated nickel catalyst described in the present invention has good catalytic hydrogenation performance in high temperature, high pressure and weakly acidic solution.

[0024] In a third aspect, the present invention provides use of the carbon-coated nickel catalyst described in the second aspect in preparing sorbitol by hydrogenation of glucose.

[0025] The application specifically comprises the following steps:

[0026] (1) Anhydrous glucose is used as a raw material, water is used as a solvent, a carbon-coated nickel catalyst is added and mixed evenly, and then transferred to a high-pressure reactor, wherein the mass ratio of the carbon-coated nickel catalyst, water and glucose is 0.009-0.021:2-5:1;

[0027] (2) Before the temperature is raised to react, the reaction system is fully replaced with N2, and then the reaction system is fully replaced with H2. After the temperature is raised to the reaction temperature, hydrogen is introduced to start the reaction. The reaction conditions are: temperature 110-150°C, hydrogen pressure 1.0-5.0 MPa, and the product sorbitol is obtained after sufficient reaction. In the above application, after the reaction is completed, the reaction liquid is filtered and analyzed by gas chromatography to calculate the conversion rate and selectivity of the reaction.

[0028] In the application, increasing the amount of catalyst is beneficial to improving the hydrogenation activity of glucose.

[0029] In the application, the reaction temperature is preferably 110-130°C.

[0030] The method for preparing the carbon-coated nickel catalyst of the present invention has a small particle size of the prepared Ni particles, and the outer carbon layer can well wrap the active metal inside, so that the Ni metal is highly dispersed inside the carbon layer, and the presence of the surface carbon layer can also effectively prevent the oxidation and loss of the active components of the catalyst. The carbon layer itself does not have any catalytic hydrogenation activity, but the internal Ni NPs transmit electrons through the middle carbon layer to the outermost carbon layer, so that the surface carbon layer has a higher electron density, so that it has the ability to catalyze hydrogenation. In the process of preparing sorbitol by hydrogenation of glucose, H2 is first adsorbed on the surface of the electron-rich carbon layer, and active hydrogen atoms H* are generated under the action of the hydrogenation active center of the carbon layer, and are quickly transferred to the substrate glucose also adsorbed on the surface of the carbon layer, reducing the carbonyl -C=O to -OH. In a high temperature, high pressure and weakly acidic reaction environment, the catalyst has good conversion rate and selectivity while maintaining good long-term cycle stability and regeneration performance.

[0031] Therefore, controlling the thickness, density, and electron transmission capacity of the carbon layer is the key to determining the performance of the catalyst. Different metal precursors have different interactions with carbon source compounds. The present invention controls the carbon source compound, carbonization temperature, and carbonization time to obtain a suitable carbon layer thickness and carbon layer structure, which is convenient for exerting the quantum tunneling effect and obtaining a catalyst with excellent performance under high temperature, high pressure, and weakly acidic conditions.

[0032] Compared with the prior art, the present invention has the following advantages:

[0033] 1. Since the metal nickel catalyst is covered by a carbon layer, when it is in a high temperature and high pressure or weakly acidic environment, the metal nickel will not be lost, sintered, oxidized, etc., causing the catalyst to be deactivated. Therefore, the catalyst of the present invention has good stability in a harsh reaction environment, and the catalyst was used for 8 consecutive times without obvious deactivation.

[0034] 2. The reaction of preparing sorbitol by catalytic hydrogenation of glucose under the action of the carbon-coated nickel catalyst used in the present invention has better stability and target product selectivity than the nickel-based catalyst not coated with carbon. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 : TEM images of the carbon-coated structure of the carbon-coated nickel catalyst prepared in Example 6 at different magnifications.

[0036] Figure 2 : XRD patterns of the fresh carbon-coated nickel catalyst prepared in Example 6 and the carbon-coated nickel catalyst after being used 8 times.

[0037] Figure 3 : N2 adsorption-desorption curve and pore size distribution curve of the carbon-coated nickel catalyst prepared in Example 6. DETAILED DESCRIPTION

[0038] The present invention is further described below by means of specific embodiments, but the protection scope of the present invention is not limited thereto.

[0039] Embodiment Adopt high performance gas chromatography to carry out quantitative analysis to sorbitol, first reacted solution is carried out acetylation reaction, specific experimental steps are as follows: take 0.2mL sample solution in stopper test tube, add 0.3mL methylimidazole and 2mL acetic anhydride successively, acetylation reaction 10min at room temperature. Then add 5mL distilled water to degrade excessive acetic anhydride, use flowing tap water to cool to room temperature, add 1mL chloroform, shake to make it fully mixed. After standing for 10min, suck off upper aqueous phase, add 3mL distilled water again, cool, add 1mL chloroform, stand for stratification, suck off aqueous phase, repeat three times. Add appropriate amount of anhydrous sodium sulfate dehydration drying in the lower chloroform phase obtained, stand for 5min, draw a small amount of solution and carry out gas chromatographic analysis.

[0040] The samples after acetylation reaction were analyzed by Agilent 7890B gas chromatograph produced by Agilent Technologies Co., Ltd. The optimized chromatographic conditions were as follows: using a capillary column HP-5 (30m×320μm×0.25μm); the initial column temperature was set to 180℃, increased to 220℃ at 4℃ / min, and maintained at 220℃ for 15min; the vaporization chamber temperature was set to 270℃; FID hydrogen flame detector; injection volume was 1μL; carrier gas was He, the flow rate was 1mL / min, and the split ratio was 10:1.

[0041] Example 1

[0042] Take 1g SiO2 carrier in a beaker, add 50ml deionized water, then take 4.25ml Ni(NO3)2·6H2O with a salt concentration of 0.5g / mL and add it to the above solution, stir in a water bath at 80℃ for 4h, then slowly add a small amount of ammonia water of a certain concentration until the solution pH = 12, and continue stirring for 4h. Cool to room temperature, filter, wash with deionized water until neutral, vacuum dry at 70℃ for 12h, then heat the obtained product to 550℃ in air atmosphere and roast for 4h to obtain black powder, finally transfer to a tubular furnace, pass a constant H2 gas flow, program the temperature to 300℃ for reduction for 3h, and obtain Ni / SiO2 catalyst, which is sealed with ethanol for preservation.

[0043] Weigh 1 g of the catalyst prepared above, mix it evenly with 50 ml of water, add 1.179 g of monohydrated glucose, a soluble sugar carbon source compound, soak at room temperature for 10 h, and then vacuum dry at 60 ° C for 15 h until the water is dried to obtain a dry product. The obtained dry product is calcined at 650 ° C for 6 h under N2 atmosphere to obtain a carbon-coated nickel catalyst.

[0044] Example 2

[0045] Take 1g TiO2 carrier in a beaker, add 50ml deionized water, then take 3.47ml NiCl2·6H2O with a salt concentration of 0.5g / mL and add it to the above solution and stir in a water bath at 80℃ for 4h, then slowly add a small amount of ammonia water of a certain concentration until the solution pH = 12, and continue stirring for 4h. Cool to room temperature, filter, wash with deionized water until neutral, vacuum dry at 70℃ for 12h, then heat the obtained product to 500℃ in a nitrogen atmosphere and calcine for 4h to obtain black powder, finally transfer to a tubular furnace, pass a constant H2 gas flow, program the temperature to 500℃ for reduction for 5h, and obtain Ni / TiO2 catalyst, which is then sealed with ethanol for preservation.

[0046] Weigh 1 g of the catalyst prepared above, mix it evenly with 50 ml of water, add 1.179 g of soluble sugar carbon source compound soluble starch, soak at room temperature for 8 hours, and vacuum dry at 70°C for 12 hours until the water is dried to obtain a dry product. The obtained dry product is calcined at 750°C for 4 hours under N2 atmosphere to obtain a carbon-coated nickel catalyst.

[0047] Example 3

[0048] Take 1g of activated carbon carrier in a beaker, add 50ml of deionized water, then take 3.63ml of Ni(CH3COO)2·4H2O with a salt concentration of 0.5g / mL and add it to the above solution and stir in a water bath at 80℃ for 4h, then slowly add a small amount of ammonia water of a certain concentration until the solution pH = 12, and continue stirring for 4h. Cool to room temperature, filter, wash with deionized water until neutral, vacuum dry at 70℃ for 12h, then heat the obtained product to 500℃ in an argon atmosphere and calcine for 8h to obtain a black powder, finally transfer to a tubular furnace, pass a constant H2 gas flow, program the temperature to 400℃ for reduction for 3h, and obtain a Ni / C catalyst, which is then sealed with ethanol for preservation.

[0049] Weigh 1 g of the catalyst prepared above, mix it evenly with 50 ml of water, add 1.252 g of citric acid monohydrate, a soluble sugar carbon source compound, soak at room temperature for 5 hours, and then vacuum dry at 100°C for 6 hours until the water is dried to obtain a dry product. The obtained dry product is calcined at 900°C for 7 hours under N2 atmosphere to obtain a carbon-coated nickel catalyst.

[0050] Example 4

[0051] Take 1g of diatomaceous earth carrier in a beaker, add 50ml of deionized water, then take 3.84ml of NiSO4·6H2O with a salt concentration of 0.5g / mL and add it to the above solution, stir in a water bath at 80℃ for 4h, then slowly add a small amount of ammonia water of a certain concentration until the solution pH = 12, and continue stirring for 4h. Cool to room temperature, filter, wash with deionized water until neutral, vacuum dry at 70℃ for 12h, then heat the obtained product to 800℃ in a helium atmosphere and calcine for 7h to obtain a black powder, finally transfer to a tubular furnace, pass a constant H2 gas flow, program the temperature to 350℃ for reduction for 9h, and obtain a Ni / diatomaceous earth catalyst, which is sealed with ethanol for preservation.

[0052] Weigh 1 g of the catalyst prepared above, mix it evenly with 50 ml of water, add 0.663 g of PVP, soak at room temperature for 4 h, and then vacuum dry at 90 ° C for 8 h until the water is dried to obtain a dry product. The obtained dry product is calcined at 700 ° C for 5 h under N2 atmosphere to obtain a carbon-coated nickel catalyst.

[0053] Example 5

[0054] Take 1g of activated carbon carrier in a beaker, add 50ml of deionized water, then take 2.48ml of Ni(NO3)2·6H2O with a salt concentration of 0.5g / mL and add it to the above solution and stir in a water bath at 80℃ for 4h, then slowly add a small amount of ammonia water of a certain concentration until the solution pH = 12, and continue stirring for 4h. Cool to room temperature, filter, wash with deionized water until neutral, vacuum dry at 70℃ for 12h, then heat the obtained product to 700℃ in a nitrogen atmosphere and calcine for 7h to obtain a black powder, finally transfer to a tubular furnace, pass a constant H2 gas flow, program the temperature to 300℃ for reduction for 4h, and obtain a Ni / activated carbon catalyst, and the obtained catalyst is sealed with ethanol for preservation.

[0055] Weigh 1 g of the catalyst prepared above, mix it evenly with 50 ml of water, add 1.019 g of soluble sugar carbon source compound sucrose, soak at room temperature for 4 hours, and vacuum dry at 50°C for 15 hours until the water is dried to obtain a dry product. The obtained dry product is calcined at 800°C for 4 hours under N2 atmosphere to obtain a carbon-coated nickel catalyst.

[0056] Example 6

[0057] Take 1g of activated carbon carrier in a beaker, add 50ml of deionized water, then take 3.30ml of Ni(NO3)2·6H2O with a salt concentration of 0.5g / mL and add it to the above solution and stir in a water bath at 80℃ for 4h, then slowly add a small amount of ammonia water of a certain concentration until the solution pH = 12, and continue stirring for 4h. Cool to room temperature, filter, wash with deionized water until neutral, vacuum dry at 70℃ for 12h, then heat the obtained product to 500℃ in an air atmosphere and calcine for 5h to obtain a black powder, finally transfer to a tubular furnace, pass a constant H2 gas flow, program the temperature to 400℃ for reduction for 5h, and obtain a Ni / activated carbon catalyst, and the obtained catalyst is sealed with ethanol for preservation.

[0058] Weigh 1 g of the catalyst prepared above, mix it evenly with 50 ml of water, add 1.179 g of monohydrated glucose, a soluble sugar carbon source compound, soak at room temperature for 8 h, and then vacuum dry at 70 ° C for 12 h until the water is dried to obtain a dry product. The obtained dry product is calcined at 600 ° C for 6 h under N2 atmosphere to obtain a carbon-coated nickel catalyst.

[0059] Example 7

[0060] In a 100mL autoclave, add 0.1g of the catalyst prepared in Example 1, 10g of glucose, and 30mL of deionized water, replace the air with nitrogen five times, and then fill with 1MPa of N2 gas, keep it for 3-5min, and check the air tightness of the device. If the air tightness is good, evacuate the gas in the autoclave, and then replace the nitrogen in the reactor with hydrogen three times, heat it to 120°C and pass hydrogen to keep its pressure at 4.0Mpa, start stirring, stir at a rate of 1000 rpm, and obtain the product sorbitol after sufficient reaction. Take out the reaction solution, filter to remove the catalyst, and analyze it with high-performance gas chromatography. The glucose conversion rate is 97.4% and the sorbitol selectivity is 72.0%.

[0061] Example 8

[0062] In a 100mL autoclave, add 0.2g of the catalyst prepared in Example 2, 20g of glucose, and 40mL of deionized water, replace the air with nitrogen five times, then fill with 1MPa of N2 gas, keep for 3-5min, and check the air tightness of the device. If the air tightness is good, then evacuate the gas in the autoclave, then replace the nitrogen in the reactor with hydrogen three times, heat to 110°C and pass hydrogen to maintain its pressure of 5.0Mpa, start stirring, stir at a speed of 1000 rpm, and obtain the product sorbitol after sufficient reaction. Take out the reaction solution, filter to remove the catalyst, and analyze with high-efficiency gas chromatography. The glucose conversion rate is 95.2% and the sorbitol selectivity is 81.7%.

[0063] Example 9

[0064] In a 100mL autoclave, add 0.5g of the catalyst prepared in Example 3, 50g of glucose, and 50mL of deionized water, replace the air with nitrogen five times, then fill with 1MPa of N2 gas, keep for 3-5min, and check the air tightness of the device. If the air tightness is good, then evacuate the gas in the autoclave, then replace the nitrogen in the reactor with hydrogen three times, heat to 130°C and pass hydrogen to maintain its pressure at 4.0Mpa, start stirring, stir at a speed of 1000 rpm, and obtain the product sorbitol after sufficient reaction. Take out the reaction solution, filter to remove the catalyst, and analyze with high-efficiency gas chromatography. The glucose conversion rate is 97.3% and the sorbitol selectivity is 88.6%.

[0065] Example 10

[0066] In a 100mL autoclave, add 0.4g of the catalyst prepared in Example 4, 20g of glucose, and 20mL of deionized water, replace the air with nitrogen five times, then fill with 1MPa of N2 gas, keep for 3-5min, and check the air tightness of the device. If the air tightness is good, then evacuate the gas in the autoclave, then replace the nitrogen in the reactor with hydrogen three times, heat to 110°C and pass hydrogen to maintain its pressure of 2.0Mpa, start stirring, stir at a rate of 1000 rpm, and obtain the product sorbitol after sufficient reaction. Take out the reaction solution, filter to remove the catalyst, and analyze with high-performance gas chromatography. The glucose conversion rate is 95.6% and the sorbitol selectivity is 83.4%.

[0067] Embodiment 11

[0068] In a 100mL autoclave, add 0.3g of the catalyst prepared in Example 5, 10g of glucose, and 40mL of deionized water, replace the air with nitrogen five times, and then fill with 1MPa of N2 gas, keep for 3-5min, and check the air tightness of the device. If the air tightness is good, then evacuate the gas in the autoclave, then replace the nitrogen in the reactor with hydrogen three times, heat to 110°C and pass hydrogen to maintain its pressure of 1.0Mpa, start stirring, stir at a speed of 1000 rpm, and obtain the product sorbitol after sufficient reaction. Take out the reaction solution, filter to remove the catalyst, and analyze with high-efficiency gas chromatography. The glucose conversion rate is 90.8% and the sorbitol selectivity is 73.0%.

[0069] Example 12

[0070] In a 100mL autoclave, add 0.6g of the catalyst prepared in Example 6, 20g of glucose, and 30mL of deionized water, replace the air with nitrogen five times, and then fill with 1MPa of N2 gas, keep it for 3-5min, and check the air tightness of the device. If the air tightness is good, then evacuate the gas in the autoclave, and then replace the nitrogen in the reactor with hydrogen three times, heat it to 110°C and pass hydrogen to maintain its pressure at 4.0Mpa, start stirring, stir at a rate of 1000 rpm, and obtain the product sorbitol after sufficient reaction. Take out the reaction solution, filter to remove the catalyst, and analyze it with high-performance gas chromatography. The glucose conversion rate is 99.8% and the sorbitol selectivity is 97.5%.

[0071] Embodiment 13

[0072] In a 100mL autoclave, add 0.6g of the catalyst prepared in Example 6, 20g of glucose, and 30mL of deionized water, replace the air with nitrogen five times, and then fill with 1MPa of N2 gas, keep it for 3-5min, and check the air tightness of the device. If the air tightness is good, evacuate the gas in the autoclave, and then replace the nitrogen in the reactor with hydrogen three times, heat it to 110°C and pass hydrogen to maintain its pressure at 4.0Mpa, start stirring, and stir at a rate of 1000 rpm. After sufficient reaction, the product sorbitol is obtained. Take out the reaction solution, filter to remove the catalyst, analyze it with high-performance gas chromatography, and recover the obtained catalyst for application experiment. The reaction conditions are the same as above. The results are shown in Table 1.

[0073] Table 1

[0074]

[0075]

[0076] Comparative Example 1

[0077] Comparative Example 1 investigated the performance of supported carbon-encapsulated nickel metal catalysts prepared from different carbon sources. Compared with the catalyst of Example 6, replacing the carbon source with soluble starch significantly reduced the selectivity of sorbitol.

[0078] Take 1g of activated carbon carrier in a beaker, add 50ml of deionized water, then take 3.30ml of Ni(NO3)2·6H2O with a salt concentration of 0.5g / mL and add it to the above solution and stir in a water bath at 80℃ for 4h, then slowly add a small amount of ammonia water of a certain concentration until the solution pH = 12, and continue stirring for 4h. Cool to room temperature, filter, wash with deionized water until neutral, vacuum dry at 70℃ for 12h, then heat the obtained product to 500℃ in an air atmosphere and calcine for 5h to obtain a black powder, finally transfer to a tubular furnace, pass a constant H2 gas flow, program the temperature to 400℃ for reduction for 5h, and obtain a Ni / activated carbon catalyst, and the obtained catalyst is sealed with ethanol for preservation.

[0079] Weigh 1 g of the catalyst prepared above, mix it evenly with 50 ml of water, add 1.179 g of soluble sugar carbon source compound soluble starch, soak at room temperature for 8 hours, and then vacuum dry at 70°C for 12 hours until the water is dried to obtain a dry product. The obtained dry product is calcined at 600°C for 6 hours under N2 atmosphere to obtain a carbon-coated nickel catalyst.

[0080] In a 100mL autoclave, add 0.6g of the catalyst prepared in Comparative Example 1, 20g of glucose, and 30mL of deionized water, replace the air with nitrogen five times, and then fill with 1MPa of N2 gas, keep for 3-5min, and check the air tightness of the device. If the air tightness is good, then evacuate the gas in the autoclave, and then replace the nitrogen in the reactor with hydrogen three times, and then introduce hydrogen to maintain its pressure at 4.0Mpa after heating to 110°C, start stirring, and stir at a rate of 1000 rpm. After sufficient reaction, the product sorbitol is obtained. Take out the reaction solution, filter to remove the catalyst, and analyze it with high-efficiency gas chromatography. The glucose conversion rate is 96.8%, and the sorbitol selectivity is 77.5%.

[0081] Comparative Example 2

[0082] Comparative Example 2 investigated the performance of a supported carbon-encapsulated nickel metal catalyst prepared at a lower carbonization temperature. Compared with the catalyst in Example 6, lowering the carbonization temperature significantly reduced the sorbitol selectivity.

[0083] Take 1g of activated carbon carrier in a beaker, add 50ml of deionized water, then take 3.30ml of Ni(NO3)2·6H2O with a salt concentration of 0.5g / mL and add it to the above solution and stir in a water bath at 80℃ for 4h, then slowly add a small amount of ammonia water of a certain concentration until the solution pH = 12, and continue stirring for 4h. Cool to room temperature, filter, wash with deionized water until neutral, vacuum dry at 70℃ for 12h, then heat the obtained product to 500℃ in an air atmosphere and calcine for 5h to obtain a black powder, finally transfer to a tubular furnace, pass a constant H2 gas flow, program the temperature to 400℃ for reduction for 5h, and obtain a Ni / activated carbon catalyst, and the obtained catalyst is sealed with ethanol for preservation.

[0084] Weigh 1 g of the catalyst prepared above, mix it evenly with 50 ml of water, add 1.179 g of monohydrated glucose, a soluble sugar carbon source compound, soak at room temperature for 8 h, and then vacuum dry at 70 ° C for 12 h until the water is dried to obtain a dry product. The obtained dry product is calcined at 500 ° C for 6 h under N2 atmosphere to obtain a carbon-coated nickel catalyst.

[0085] In a 100mL autoclave, add 0.6g of the catalyst prepared in Comparative Example 2, 20g of glucose, and 30mL of deionized water, replace the air with nitrogen five times, then fill with 1MPa of N2 gas, keep for 3-5min, and check the air tightness of the device. If the air tightness is good, then evacuate the gas in the autoclave, then replace the nitrogen in the reactor with hydrogen three times, heat to 110°C and pass hydrogen to maintain its pressure at 4.0Mpa, start stirring, stir at a rate of 1000 rpm, and obtain the product sorbitol after sufficient reaction. Take out the reaction solution, filter to remove the catalyst, and analyze with high-efficiency gas chromatography. The glucose conversion rate is 95.8% and the sorbitol selectivity is 78.5%.

[0086] Comparative Example 3

[0087] Comparative Example 3 investigated the performance of the supported carbon-encapsulated nickel metal catalyst prepared at a higher carbonization temperature. Compared with the catalyst in Example 6, increasing the carbonization temperature significantly reduced the glucose conversion rate and sorbitol selectivity.

[0088] Take 1g of activated carbon carrier in a beaker, add 50ml of deionized water, then take 3.30ml of Ni(NO3)2·6H2O with a salt concentration of 0.5g / mL and add it to the above solution and stir in a water bath at 80℃ for 4h, then slowly add a small amount of ammonia water of a certain concentration until the solution pH = 12, and continue stirring for 4h. Cool to room temperature, filter, wash with deionized water until neutral, vacuum dry at 70℃ for 12h, then heat the obtained product to 500℃ in an air atmosphere and calcine for 5h to obtain a black powder, finally transfer to a tubular furnace, pass a constant H2 gas flow, program the temperature to 400℃ for reduction for 5h, and obtain a Ni / activated carbon catalyst, and the obtained catalyst is sealed with ethanol for preservation.

[0089] Weigh 1 g of the catalyst prepared above, mix it evenly with 50 ml of water, add 1.179 g of monohydrated glucose, a soluble sugar carbon source compound, soak at room temperature for 8 h, and then vacuum dry at 70 ° C for 12 h until the water is dried to obtain a dry product. The obtained dry product is calcined at 800 ° C for 6 h under N2 atmosphere to obtain a carbon-coated nickel catalyst.

[0090] In a 100mL autoclave, add 0.6g of the catalyst prepared in Comparative Example 3, 20g of glucose, and 30mL of deionized water, replace the air with nitrogen five times, and then fill with 1MPa of N2 gas, keep for 3-5min, and check the air tightness of the device. If the air tightness is good, then evacuate the gas in the autoclave, and then replace the nitrogen in the reactor with hydrogen three times, and then introduce hydrogen to maintain its pressure at 4.0Mpa after heating to 110°C, start stirring, and stir at a rate of 1000 rpm. After sufficient reaction, the product sorbitol is obtained. Take out the reaction solution, filter to remove the catalyst, and analyze it with high-efficiency gas chromatography. The glucose conversion rate is 73.4% and the sorbitol selectivity is 72.6%.

[0091] Comparative Example 4

[0092] Comparative Example 4 investigates the performance of a supported carbon-coated nickel metal catalyst prepared with less carbon source.

[0093] Take 1g of activated carbon carrier in a beaker, add 50ml of deionized water, then take 3.30ml of Ni(NO3)2·6H2O with a salt concentration of 0.5g / mL and add it to the above solution and stir in a water bath at 80℃ for 4h, then slowly add a small amount of ammonia water of a certain concentration until the solution pH = 12, and continue stirring for 4h. Cool to room temperature, filter, wash with deionized water until neutral, vacuum dry at 70℃ for 12h, then heat the obtained product to 500℃ in an air atmosphere and calcine for 5h to obtain a black powder, finally transfer to a tubular furnace, pass a constant H2 gas flow, program the temperature to 400℃ for reduction for 5h, and obtain a Ni / activated carbon catalyst, and the obtained catalyst is sealed with ethanol for preservation.

[0094] Weigh 1 g of the catalyst prepared above, mix it evenly with 50 ml of water, add 0.589 g of monohydrated glucose, a soluble sugar carbon source compound, soak at room temperature for 8 h, and then vacuum dry at 70 ° C for 12 h until the water is dried to obtain a dry product. The obtained dry product is calcined at 600 ° C for 6 h under N2 atmosphere to obtain a carbon-coated nickel catalyst.

[0095] In a 100mL autoclave, add 0.6g of the catalyst prepared in Comparative Example 4, 20g of glucose, and 30mL of deionized water, replace the air with nitrogen five times, and then fill with 1MPa of N2 gas, keep it for 3-5min, and check the air tightness of the device. If the air tightness is good, then evacuate the gas in the autoclave, then replace the nitrogen in the reactor with hydrogen three times, heat it to 110°C and pass hydrogen to keep its pressure at 4.0Mpa, start stirring, stir at a rate of 1000 rpm, and obtain the product sorbitol after sufficient reaction. Take out the reaction solution, filter to remove the catalyst, and analyze it with high-performance gas chromatography. The glucose conversion rate is 98.4% and the sorbitol selectivity is 97.6%.

[0096] Comparative Example 5

[0097] Comparative Example 5 investigates the performance of a supported carbon-coated nickel metal catalyst prepared with a relatively large amount of carbon source.

[0098] Take 1g of activated carbon carrier in a beaker, add 50ml of deionized water, then take 3.30ml of Ni(NO3)2·6H2O with a salt concentration of 0.5g / mL and add it to the above solution and stir in a water bath at 80℃ for 4h, then slowly add a small amount of ammonia water of a certain concentration until the solution pH = 12, and continue stirring for 4h. Cool to room temperature, filter, wash with deionized water until neutral, vacuum dry at 70℃ for 12h, then heat the obtained product to 500℃ in an air atmosphere and calcine for 5h to obtain a black powder, finally transfer to a tubular furnace, pass a constant H2 gas flow, program the temperature to 400℃ for reduction for 5h, and obtain a Ni / activated carbon catalyst, and the obtained catalyst is sealed with ethanol for preservation.

[0099] Weigh 1 g of the catalyst prepared above, mix it evenly with 50 ml of water, add 2.358 g of monohydrated glucose, a soluble sugar carbon source compound, soak at room temperature for 8 h, and then vacuum dry at 70 ° C for 12 h until the water is dried to obtain a dry product. The obtained dry product is calcined at 600 ° C for 6 h under N2 atmosphere to obtain a carbon-coated nickel catalyst.

[0100] In a 100mL autoclave, add 0.6g of the catalyst prepared in Comparative Example 5, 20g of glucose, and 30mL of deionized water, replace the air with nitrogen five times, and then fill with 1MPa of N2 gas, keep it for 3-5min, and check the air tightness of the device. If the air tightness is good, then evacuate the gas in the autoclave, then replace the nitrogen in the reactor with hydrogen three times, heat it to 110°C and pass hydrogen to keep its pressure at 4.0Mpa, start stirring, stir at a rate of 1000 rpm, and obtain the product sorbitol after sufficient reaction. Take out the reaction solution, filter to remove the catalyst, and analyze it with high-performance gas chromatography. The glucose conversion rate is 93.1% and the sorbitol selectivity is 94.1%.

[0101] Comparative Example 6

[0102] Comparative Example 6 investigated the performance of the supported carbon-coated nickel metal catalyst prepared with a longer calcination time.

[0103] Take 1g of activated carbon carrier in a beaker, add 50ml of deionized water, then take 3.30ml of Ni(NO3)2·6H2O with a salt concentration of 0.5g / mL and add it to the above solution and stir in a water bath at 80℃ for 4h, then slowly add a small amount of ammonia water of a certain concentration until the solution pH = 12, and continue stirring for 4h. Cool to room temperature, filter, wash with deionized water until neutral, vacuum dry at 70℃ for 12h, then heat the obtained product to 500℃ in an air atmosphere and calcine for 5h to obtain a black powder, finally transfer to a tubular furnace, pass a constant H2 gas flow, program the temperature to 400℃ for reduction for 5h, and obtain a Ni / activated carbon catalyst, and the obtained catalyst is sealed with ethanol for preservation.

[0104] Weigh 1 g of the catalyst prepared above, mix it evenly with 50 ml of water, add 1.179 g of monohydrated glucose, a soluble sugar carbon source compound, soak at room temperature for 8 h, and then vacuum dry at 70 ° C for 12 h until the water is dried to obtain a dry product. The obtained dry product is calcined at 600 ° C for 10 h under N2 atmosphere to obtain a carbon-coated nickel catalyst.

[0105] In a 100mL autoclave, add 0.6g of the catalyst prepared in Comparative Example 6, 20g of glucose, and 30mL of deionized water, replace the air with nitrogen five times, and then fill with 1MPa of N2 gas, keep it for 3-5min, and check the air tightness of the device. If the air tightness is good, then evacuate the gas in the autoclave, then replace the nitrogen in the reactor with hydrogen three times, heat it to 110°C and pass hydrogen to keep its pressure at 4.0Mpa, start stirring, stir at a rate of 1000 rpm, and obtain the product sorbitol after sufficient reaction. Take out the reaction solution, filter to remove the catalyst, and analyze it with high-performance gas chromatography. The glucose conversion rate is 91.1% and the sorbitol selectivity is 93.2%.

[0106] Comparative Example 7

[0107] Comparative Example 7 investigated the performance of the supported carbon-encapsulated nickel metal catalyst prepared with a shorter calcination time.

[0108] Take 1g of activated carbon carrier in a beaker, add 50ml of deionized water, then take 3.30ml of Ni(NO3)2·6H2O with a salt concentration of 0.5g / mL and add it to the above solution and stir in a water bath at 80℃ for 4h, then slowly add a small amount of ammonia water of a certain concentration until the solution pH = 12, and continue stirring for 4h. Cool to room temperature, filter, wash with deionized water until neutral, vacuum dry at 70℃ for 12h, then heat the obtained product to 500℃ in an air atmosphere and calcine for 5h to obtain a black powder, finally transfer to a tubular furnace, pass a constant H2 gas flow, program the temperature to 400℃ for reduction for 5h, and obtain a Ni / activated carbon catalyst, and the obtained catalyst is sealed with ethanol for preservation.

[0109] Weigh 1 g of the catalyst prepared above, mix it evenly with 50 ml of water, add 1.179 g of monohydrated glucose, a soluble sugar carbon source compound, soak at room temperature for 8 h, and then vacuum dry at 70 ° C for 12 h until the water is dried to obtain a dry product. The obtained dry product is calcined at 600 ° C for 2 h under N2 atmosphere to obtain a carbon-coated nickel catalyst.

[0110] In a 100mL autoclave, add 0.6g of the catalyst prepared in Comparative Example 7, 20g of glucose, and 30mL of deionized water, replace the air with nitrogen five times, and then fill with 1MPa of N2 gas, keep for 3-5min, and check the air tightness of the device. If the air tightness is good, then evacuate the gas in the autoclave, then replace the nitrogen in the reactor with hydrogen three times, heat to 110°C and pass hydrogen to maintain its pressure at 4.0Mpa, start stirring, stir at a rate of 1000 rpm, and obtain the product sorbitol after sufficient reaction. Take out the reaction solution, filter to remove the catalyst, and analyze with high-performance gas chromatography. The glucose conversion rate is 90.3% and the sorbitol selectivity is 93.5%.

[0111] Comparative Example 8

[0112] Comparative Example 8 investigated the performance of the supported nickel catalyst without carbon coating.

[0113] Take 1g of activated carbon carrier in a beaker, add 50ml of deionized water, then take 3.30ml of Ni(NO3)2·6H2O with a salt concentration of 0.5g / mL and add it to the above solution and stir in a water bath at 80℃ for 4h, then slowly add a small amount of ammonia water of a certain concentration until the solution pH = 12, and continue stirring for 4h. Cool to room temperature, filter, wash with deionized water until neutral, vacuum dry at 70℃ for 12h, then heat the obtained product to 500℃ in an air atmosphere and calcine for 5h to obtain a black powder, finally transfer to a tubular furnace, pass a constant H2 gas flow, program the temperature to 400℃ for reduction for 5h, and obtain a Ni / activated carbon catalyst, and the obtained catalyst is sealed with ethanol for preservation.

[0114] In a 100mL autoclave, add 0.6g of the catalyst prepared in Comparative Example 8, 20g of glucose, and 30mL of deionized water, replace the air with nitrogen five times, and then fill with 1MPa of N2 gas, keep it for 3-5min, and check the air tightness of the device. If the air tightness is good, evacuate the gas in the autoclave, and then replace the nitrogen in the reactor with hydrogen three times, heat it to 110°C and pass hydrogen to maintain its pressure at 4.0Mpa, start stirring, and stir at a rate of 1000 rpm. After sufficient reaction, the product sorbitol is obtained. Take out the reaction solution, filter to remove the catalyst, analyze it with high-performance gas chromatography, and recover the catalyst for application experiment. The reaction conditions are the same as above, and the results are shown in Table 2.

[0115] Table 2

[0116]

[0117]

Claims

1. A method for preparing a carbon-coated nickel catalyst for preparing sorbitol by hydrogenation of glucose, characterized in that: The preparation method comprises the following steps: Step 1: Preparation of supported nickel catalyst: disperse the carrier in water, add the nickel precursor solution, stir in a water bath at 70-90°C for 3-6h, then add ammonia water dropwise to adjust the pH to 12 to allow the nickel ions to fully precipitate, continue stirring for 0.5-5h, cool to room temperature, filter, wash with water until neutral, and vacuum dry until the water is dried to obtain a dry product; calcine the obtained dry product at 500-800°C in an inert atmosphere or air atmosphere for 4-8h to obtain a calcined product, and finally transfer to a tubular furnace, introduce a constant H2 gas flow, and program the temperature to 300-500°C for reduction for 3-9h to obtain a supported nickel catalyst; Step 2: uniformly mix the supported nickel catalyst and water, add a soluble sugar carbon source compound, soak at room temperature for 4 to 10 hours, and then vacuum dry until the water is dried to obtain a dry product; The obtained dry product is calcined at 400-900°C for 4-10h under N2 atmosphere to finally obtain the desired carbon-coated nickel catalyst; the soluble sugar carbon source compound is selected from one of monohydrated glucose, soluble starch, monohydrated citric acid, PVP or sucrose; the mass of carbon element in the soluble sugar carbon source compound accounts for 10-50% of the mass of the supported nickel catalyst, preferably 20-50%, more preferably 35-50%, and further preferably 40-45%.

2. The preparation method according to claim 1, characterized in that: The carrier of the supported nickel catalyst is activated carbon, SiO2, TiO2 or diatomaceous earth.

3. The preparation method according to claim 1, characterized in that: In step 1, the carrier and the nickel precursor solution are added according to the required theoretical loading amount of nickel, specifically, the theoretical loading amount of nickel = m Ni / m 载体 ×100%=20-45%, preferably 25-45%, more preferably 30-35%; wherein m Ni It refers to the mass of Ni element contained in the nickel precursor solution.

4. The preparation method according to claim 1, characterized in that: In step 1, the obtained dry product is calcined at 500°C for 5 hours in an inert atmosphere or an air atmosphere to obtain a calcined product, and finally transferred to a tubular furnace, a constant flow of H2 is introduced, and the temperature is programmed to 400°C for reduction for 5 hours.

5. The preparation method according to claim 1, characterized in that: In step 2, the calcination temperature is 500-800°C.

6. The preparation method according to claim 1, characterized in that: In step 2, the calcination temperature is 550-650°C.

7. The preparation method according to claim 1, characterized in that: In step 2, calcination is performed at 600°C for 6 hours.

8. A carbon-coated nickel catalyst for preparing sorbitol by hydrogenating glucose, prepared according to the preparation method of any one of claims 1 to 7.

9. Use of the carbon-coated nickel catalyst as claimed in claim 8 in preparing sorbitol by hydrogenation of glucose.

10. The use according to claim 9, characterized in that: The application specifically comprises the following steps: (1) Anhydrous glucose is used as a raw material, water is used as a solvent, a carbon-coated nickel catalyst is added and mixed evenly, and then transferred to a high-pressure reactor, wherein the mass ratio of the carbon-coated nickel catalyst, water and glucose is 0.009-0.021:2-5:1; (2) Before heating the reaction, the reaction system is fully replaced with N2, and then with H2. After the reaction temperature is reached, hydrogen is introduced to start the reaction. The reaction conditions are: temperature 110-150°C, hydrogen pressure 1.0-5.0 MPa. After sufficient reaction, the product sorbitol is obtained.

Citation Information

Patent Citations

  • Nickel-based catalyst, and preparation method and application thereof

    CN104399468A

  • Nickel-titanium dioxide-carbon trinary nano composite catalyst and preparation method thereof

    CN104826631A

  • Loaded catalyst, preparation method thereof and preparation method of sorbitol

    CN107262137A

  • Preparation method of noble metal-based catalyst

    CN113171772A

  • Nitrogen-modified carbon-coated nickel catalyst as well as preparation method and application thereof

    CN116020511A